2017
DOI: 10.5539/ies.v10n8p128
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles of Saudi Woman Work in the Mixed Environment: A Field Study

Abstract: The study aimed to identify the obstacles facing Saudi woman while working in a mixed work environment. The main study sample consisted of (223) from the health sector female affiliates and were divided into two groups. The first group consisted of (129) participants from the health sector and workers in Riyadh, Kingdom of Saudi Arabia (KSA) hospitals. The second group involved (94) participants from the health sector and workers in Najran, KSA hospitals. The study adopted the descriptive and analytical approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In many cases, men fail to see that working in a mixed-gender environment is a major difficulty for women. Even more so in the KSA because Saudi society is staunchly patriarchal and maledominated (Al-Hazmi et al, 2017). Moreover, sexual harassment is often justified because of a lack of harassment deterrent laws and regulations (Al-Hazmi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases, men fail to see that working in a mixed-gender environment is a major difficulty for women. Even more so in the KSA because Saudi society is staunchly patriarchal and maledominated (Al-Hazmi et al, 2017). Moreover, sexual harassment is often justified because of a lack of harassment deterrent laws and regulations (Al-Hazmi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They fail to acknowledge that working in a mixed-gender environment is a major difficulty for women. As evidenced by Al-Hazmi et al (2017), this factor is amplified in the KSA because Saudi society is staunchly patriarchal and male-dominated. Moreover, sexual harassment is often justified due to an absence of harassment deterrent laws and regulations (Al-Hazmi et al, 2017).…”
Section: Barriers To Women In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Vainikolo (2017) observed that employers had different expectations of women and recruited them as their last resort to meet impromptu human resources shortages. This is supported by (AL-Hazmi et al, 2017;Martin and Barnard, 2013) who concluded that some employers perceived women working on construction sites as an obstacle.…”
Section: Discriminatory Attitudes Towards Women In Developing Countriesmentioning
confidence: 87%